Intentional Self-Regulation and Schools Climate Effects on Academic Buoyancy Mediated by Positive Youth Development - Arafah, Shofa Mutiara; Sumiati, Neneng Tati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
Academic buoyancy is the capability to handle and effectively manage daily difficulties and challenges. Therefore, the purpose of this study was to determine the role of positive youth development in mediating the relationship between intentional self-regulation, schools climate, and academic buoyancy. A quantitative method with a cross-sectional design was used, the respondents were 875 students from Madrasah Aliyah Negeri (MAN) in Tasikmalaya City, and path analysis was conducted with Mplus 8.4 software. The results showed that positive youth development mediated the relationship between intentional self-reguation, schools climate, and academic buoyancy. Furthermore, the study recommended that schools need to provide programs to facilitate positive youth development. This can be achieved through the development of positive climate and improvement of students' intentional self-reguation ability.